2008
DOI: 10.1016/j.otohns.2007.12.034
|View full text |Cite
|
Sign up to set email alerts
|

The value of narrow band imaging endoscope for early head and neck cancers

Abstract: An NBI endoscope significantly improves diagnostic accuracy, sensitivity, and negative predictive value in detecting SCCHN in EC patients. This endoscope would be highly beneficial in detecting superficial SCCHNs in high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
137
1
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(143 citation statements)
references
References 10 publications
0
137
1
5
Order By: Relevance
“…In the literature, there exist only a few publications on the exclusive use of NBI in laryngology (135)(136)(137)(138)(139)(140)(141)(142). However, several studies assessed the value of NBI in the head and neck also including the larynx (132,137,(143)(144)(145)(146)(147)(148). NBI has shown in the larynx, over last years, improved sensitivity 61-91% and specificity 87-92% (146,149) but false positives and false negatives have been reported, especially in the larynx, and increase with a short learning curve.…”
Section: Narrow Band Imaging (Nbi)mentioning
confidence: 99%
“…In the literature, there exist only a few publications on the exclusive use of NBI in laryngology (135)(136)(137)(138)(139)(140)(141)(142). However, several studies assessed the value of NBI in the head and neck also including the larynx (132,137,(143)(144)(145)(146)(147)(148). NBI has shown in the larynx, over last years, improved sensitivity 61-91% and specificity 87-92% (146,149) but false positives and false negatives have been reported, especially in the larynx, and increase with a short learning curve.…”
Section: Narrow Band Imaging (Nbi)mentioning
confidence: 99%
“…Watanabe et al (8,9) reported that the NBI rhinolaryngoscope (ENF-V2, Olympus Medical Systems) with a colourchip light source (CLV-160B, Olympus Medical Systems) improved the diagnostic accuracy, and the negative predictive values for superficial lesions in the oropharynx and hypopharynx compared with those of conventional WLI. However, there is still a critical difference in the image qualities of CCDs between gastrointestinal endoscopy and rhinolaryngoscopy.…”
Section: Head and Neck Cancermentioning
confidence: 99%
“…The NBI system (Olympus Medical System Co., Tokyo, Japan) has been already proven to be a useful diagnostic tool for identifying superficial squamous cell carcinoma of the head and neck [4][5][6][19][20][21]. Trans-nasal endoscopy can usually be performed comfortably due to attenuation of the gag reflex [22]; indeed in Japan, trans-nasal endoscopy is a very common procedure and can be performed without sedation.…”
Section: Discussionmentioning
confidence: 99%